2004
DOI: 10.1017/s1431927604040954
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Microscopy to a Better Knowledge of the Biology ofGiardia lamblia

Abstract: Giardia lamblia is a flagellated protozoan of great medical and biological importance. It is the causative agent of giardiasis, one of the most prevalent diarrheal disease both in developed and third-world countries. Morphological studies have shown that G. lamblia does not present structures such as peroxisomes, mitochondria, and a well-elaborated Golgi complex. In this review, special emphasis is given to the contribution made by various microscopic techniques to a better knowledge of the biology of the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…Additional genomes encode multiple copies of Pex11p; there are two or three copies in Archaeplastida genomes (Chlamydomonas reinhardtii, Micromonas sp., Ostreococcus tauri, Populus trichocarpa and Volvox carteri), and five copies in the rhizarian alga Bigelowiella natans and the ciliate Tetrahymena thermophila. Peroxisomes have not been reported in many parasites (de Souza et al, 2004;Gabaldón et al, 2006;Gabaldón, 2010), and it was therefore not unexpected that Pex11p was not identified in the parasite genomes analyzed in this study -Encephalitozoon cuniculi, Entamoeba histolytica, Giardia sp., Trichomonas vaginalis, Theileria parva and Plasmodium falciparum. Pex11p was identified in the parasite Toxoplasma gondii, although peroxisomes have not been observed in this organism (Ding et al, 2000).…”
Section: A Comparative Genomics Survey Of the Pex11 Protein Familymentioning
confidence: 62%
“…Additional genomes encode multiple copies of Pex11p; there are two or three copies in Archaeplastida genomes (Chlamydomonas reinhardtii, Micromonas sp., Ostreococcus tauri, Populus trichocarpa and Volvox carteri), and five copies in the rhizarian alga Bigelowiella natans and the ciliate Tetrahymena thermophila. Peroxisomes have not been reported in many parasites (de Souza et al, 2004;Gabaldón et al, 2006;Gabaldón, 2010), and it was therefore not unexpected that Pex11p was not identified in the parasite genomes analyzed in this study -Encephalitozoon cuniculi, Entamoeba histolytica, Giardia sp., Trichomonas vaginalis, Theileria parva and Plasmodium falciparum. Pex11p was identified in the parasite Toxoplasma gondii, although peroxisomes have not been observed in this organism (Ding et al, 2000).…”
Section: A Comparative Genomics Survey Of the Pex11 Protein Familymentioning
confidence: 62%
“…The vesicle grows in size and density, forming true secretory granules which migrate towards the cell periphery, fuse with the plasma membrane and discharge their content on the parasite surface. There are evidences that this process involves the participation of enzymes such as kinases and phosphatases and may, therefore, constitute targets for anti parasitic drugs [Reviews in [130][131][132].…”
Section: The Encystation Vesiclesmentioning
confidence: 99%
“…It is formed by three distinct structures: first, microtubules that are arranged in a coiled array around a bare area; second, microribbons that protrude into the cytoplasm; and third, cross bridges that connect adjacent microtubules (Elmendorf et al 2003;De Souza et al 2004;Sant'Anna et al 2005). Besides its structural organisation, it is well known that the microtubules of the adhesive disc present acetylated and poly-glycylated α-tubulin (Soltys and Gupta 1994;Weber et al 1996;Campanati et al 1999;Campanati et al 2003).…”
Section: Introductionmentioning
confidence: 99%